Development of Methodology for Modelling and Simulation of 3D Auxetic Structures - Páscoa, Frederico Tomás (2022)
As the requirements associated with mechanical behavior in structures throughout all industries become more demanding, some of the improvement needs cannot be fulfilled without exploring geometries that behave in ways which are not commonly observed. One of the behaviors that can lead to breakthroughs in several fields is the auxetic behavior, which is present in auxetic structures. With most of the basic auxetic structures, the modelling and the simulation of the mechanical behavior can be performed with methods that do not require further improvements to work. But with complex auxetic structures, the application of these methods can be insufficient for constructing models which accurately define the structures. This makes these models inadequate for use in simulations of the behavior of said structures. This work proposes a methodology that allows for the modelling of complex three dimensional functionally graded auxetic structures, realized through modifications in the equations that define the basic surfaces which characterize the aforementioned structures. In this methodology, the simulation studies are performed by means of the finite element method. The gyroid surface was used as the complex geometry from which to form the auxetic structures. Experimental testing and simulation studies were performed on geometries with different gradient types and steepness’s to obtain comprehensive data that allows to infer on the accuracy of the methodology.